Optimasi Konsentrasi Vaselin Album dan Adeps Lanae pada Formulasi Sediaan Salep Ekstrak Etanol Daun Kersen (Muntingia calabura L.) - Baiq Saomi Alfilaili; Wahida Hajrin; Yohanes Juliantoni (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2021)
Cherry leaves (Muntingia calabura L.) contain secondary metabolites such as tannins, flavonoids, and saponins. This secondary metabolite compound functions as an antibacterial, especially Staphylococcus epidermidis bacteria that cause acne, so that it can be developed into a formula. One of the dosage forms that can be developed is the ointment dosage form. The choice of base concentration is very important because it can affect the physical properties and effectiveness of the preparation. The purpose of this study was to determine the optimum composition of the ethanol extract formula of cherry leaves with variations concentration of Vaseline album and adeps lanae, physical properties and level of acceptance of the consumer formula which was declared optimal. Cherry leaves were extracted by maceration method using ethanol 96% solvent. Determination of the optimum value was carried out using the Simplex Lattice Design method available in the Design Expert software Version 11. The results showed that the optimum ointment formula had a composition of vaseline albumin and adeps lanae of 73,29% and 9,71%, with a spreadability 3,10 ± 0,12 cm, adhesion 6,10 ± 0,53 seconds, pH 4,78 ± 0,08, and the acceptability value is 4,02. So it can be concluded that the formula declared optimum has physical properties that meet the requirements and are liked by the respondents.